The Bank of Canada's 2009 Methods-of-Payment survey: Methodology and key results - Carlos Arango; Angelika Welte (Bank of Canada, 2012)
The authors present the methodology and main findings of the Bank of Canada's 2009 Methods-of-Payment survey, a detailed investigation of consumer payment behaviour in Canada. The survey targeted the 18- to 75-year-old Canadian resident population. During November 2009, participants answered a questionnaire about their demographics, personal finance, and payment instrument habits and perceptions. Of the 6,868 questionnaire respondents, about half also completed a 3-day shopping diary, recording close to 16,000 shopping transactions. The survey gives a detailed account of Canadians' cash management habits and payment instrument choices and provides important clues into the reasons why Canadians pay the way they do.
Keywords: E4; 330; Bank notes; Payment; clearing; and settlement systems; Financial services